Association between standard of living and underweight & overweight among likely to conceive women in rural North Karnataka-baseline result of DBW cohort - Gurung, Tika Ram; Kodkany, Balachandra S; Mastiholi, Shivanand; Neginhal (Gurung), Vijayalaxmi Shivanand (Indian Journal of Community Health, 2018)
Background: In 2014, approximately 462 million adults worldwide were underweight; while 1.9 billion were either overweight or obese. Hence, a study was carried out first time using the NFHS Standard of Living Index to assess the association between socioeconomic status and underweight & overweight among likely to conceive women.Material & Methods: In Determinants of Birth Weight (DBW): a community based prospective cohort study; household characteristic information was collected from 1293 likely to conceive women. Nutritional status of women was graded based on WHO international BMI categories. Chi-square test and multinomial logistic regression were applied to assess the association between standard of living and underweight & overweight with the 95% confidence level and p values less than 0.05.Results: The prevalence of underweight, normal weight, overweight and obesity was found 35.1%, 52.4%, 9.7% and 2.7%, respectively, with mean±SD BMI 20.4 kg/m2±3.876 kg/m2. The low standard of living was significantly associated with underweight whereas high standard of living was associated with overweight among likely to conceive women in a rural North Karnataka with a p value less than 0.05.Conclusion: Among likely to conceive women, there is an inverse association between standard of living and underweight whereas positive association with overweight in a rural North Karnataka.